Contemporary cases in U.S. foreign policy from terrorism to trade - Carter, Ralph G. (SAGE, 2014)
Fully updated to cover the Obama administration, all cases have been revised to reflect recent developments. Whether grappling with use-of-force questions, the international financial crisis, legal and human rights, trade issues, multilateral approaches to the nuclear programs of North Korea and Iran, or climate change, Carter's engaging case study approach encourages students to question motives, consider alternatives, and analyze outcomes.